Eksplorasi Limbah Ampas Tebu (Bagasse) untuk Material Produk Ecofashion - Marwah Anisya; Yunita Fitra Andriana; Hapiz Islamsyah (Universitas Persada Indonesia YAI, 2020)
Bagasse as sugarcane processing waste has not been widely explored as a basic material or material insmall and handicraft industries. Bagasse fiber has potential characteristics to be used as a basic materialfor disposable products with strong and resistant characteristics and a natural visual characteristic ofbeauty. The research method used a qualitative descriptive approach in exploring bagasse and itscoloring. In this research, bagasse exploration and natural coloring were carried out to find alternativesin processing bagasse into the basic material for making bags. The results of exploration and observationwere selected with the consideration that ecofashion was formulated into conceptual and proceduralfindings that were applied in processing bagasse into the basic material for making bags. In selecting thefinal product which is designed as a visual model in the form of a bag, it is determined based on theaudience response from the questionnaire distributed. The final product is a bag designed from bagasseand natural coloring that can attract the public's interest.